Presidential Term Restrictions (A Comparative Study of Indonesia and the United States in the Perspective of Constitutional Law) - Iip Rohul Wahidah; Ade Fartini (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
This study aims to compare the regulation of presidential term limits in both countries, examine their effectiveness in maintaining democratic principles, and analyze their implications for political stability and control of executive power. The method used is a normative juridical method with a comparative approach. The data used includes primary data (the 1945 Constitution and the 22nd Amendment to the US Constitution), secondary data (books, journals, and scientific articles), and tertiary data (legal dictionaries and encyclopedias of constitutional law). The results of the study show that the presidential term limit is effective in maintaining the principle of checks and balances and preventing power being centralized in one individual. The difference in regulation between Indonesia and the United States lies in the number of presidential terms and duration. In Indonesia, these restrictions serve as a correction to past experience, while in the United States, these restrictions arise after public concerns after Roosevelt's leadership. The implications of this arrangement affect political stability and the process of power rotation in both countries.